KINERJA GURU DI SEKOLAH MENENGAH KEJURUAN NEGERI KECAMATAN LUBUK BEGALUNG KOTA PADANG - Dia Permata Sari (Universitas Negeri Padang, 2018)
The goal of this research are to see information about Teachers’sperformance in vocational high School. The population are308 teachers that taken by proportional stratified randomsampling. The instrument of this research is question with Likert scale modelsthat had tested for validity and reliability. Data analyzed using mean score and performance level. The result of this research is the teachers’s performanceon vocational high Schoolin Kecamatan Lubuk Begalung Kota Padang stay in good category.The Key word: teacher, performance, vocational high school